Role of Brassinosteroids in plant growth promotion and stress tolerance during priming mediated by beneficial bacteria - Parra Pachon, Oscar Javier (SLU/Dept. of Plant Biology and Forest Genetics (until 131231), 2011)
Brassinosteroids (BR) are plant hormones widely distributed throughout the plant kingdom in low concentrations and with structural homology to animal and insect steroids. BR are involved in numerous physiological processes, and they also fulfill an antagonistic role in anti-herbivory structure formation in tomato (Campos et al., 2009). In order to characterize the role of BR upon priming with B. amyloliquefasciens 5113, gene expression analysis of BR genes was assessed in Arabidopsis thaliana. BAK1, BRI1 and DWF1 expression down-regulates, while DET2 upregulates upon bacterial priming. CPD gene expression was not affected by priming. qPCR analysis of VSP2 and PR1 were performed on BR mutants upon priming with B. amyloliquefasciens 5113. Basal levels of PR1 were higher in det2, bak1 and dwf1 compared to primed samples. Primed bri1 displayed two-fold higher expression of PR1 compared to untreated bri1. VSP2 level goes up on det2, bak1 and bri1 upon priming. No changes of VSP2 expression were observed in dwf1 upon priming. Methyl jasmonate treatment up-regulates VSP2 level twofold in det2 and nine-fold in bak1. The role of BR genes in response to insect attack was examined. BR genes appear not to be responsive to herbivory by S. littoralis. However, S. littoralis larvae fed more on BR mutants compared to those that fed on Col-0 WT. In order to understand the role of BR in JA signaling pTRV-JAR1 and pTRV-LOX2 constructs were developed and virus induced gene silencing were performed on Col-0 and BR mutants bak1 and det2. Gene silencing was confirmed by qPCR analysis of the target genes in Col-0 and det2, but not in bak1. Further insect feeding experiments are required to elucidate if BR play a role in defense responses to herbivory when JA signaling pathway is compromised.